Preliminary Analysis of Safety and Feasibility of a Single-Hole Laparoscopic Myomectomy via an Abdominal Scar Approach - Tang, Huimin; Dong, Zhiyong; Qin, Zhenyue; Zhang, Shoufeng; Wang, Huihui; Wei, Weiwei; Shi, Ruxia; Chen, Jiming; Xia, Bairong (Frontiers in Surgery, 2022)
Purpose This paper aims to explore the safety and feasibility of a single-hole laparoscopic myomectomy through an abdominal scar approach. Method The clinical data of seven patients who underwent the single-hole laparoscopic myomectomy via the abdominal scar approach from January to November 2021 in the Department of Gynecology, the Affiliated Changzhou No. 2 People's Hospital of Nanjing Medical University, were studied retrospectively. The duration of operation, the intraoperative blood loss, the decrease of postoperative hemoglobin, and the postoperative visual analogue score (0 points: no pain, 10 points: maximum pain) were recorded. Results All seven patients received the operation successfully, without changing to the conventional laparoscopic operation or open appendectomy. The average blood loss was 101.42 ± 7.89 ml, the average length of hospital stay was 5 ± 0.53 days, the average operation duration was 130 ± 26.86 min, and the 24-h pain score was 1.57 ± 0.53. The seven patients had no intraoperative or postoperative complications and no damage to the ureter or bladder. All patients could urinate spontaneously without urinary retention or urinary tract infection after catheter removal. No analgesic drugs were used after the operation. Conclusion The single-hole laparoscopic myomectomy via the abdominal scar approach is a more aesthetic and feasible option for eligible patients, but more cases and studies are needed for further confirmation.